2019
DOI: 10.2174/1872213x13666181211160238
|View full text |Cite
|
Sign up to set email alerts
|

The Inhibitory Role of M2000 (β-D-Mannuronic Acid) on Expression of Toll-like Receptor 2 and 4 in HT29 Cell Line

Abstract: Background/Objectives:Anti-inflammatory agents play a crucial role in controlling inflammatory diseases such as Inflammatory Bowel Disease (IBD) but their use is restricted due to their vast side effects. M2000 (β-D-mannuronic acid) is a new immunomodulatory drug. According to the capacity of M2000 in suppressing some molecules involved in Toll Like Receptors (TLRs) signaling and reducing oxidative stress we hypothesize that, this molecule may have a potential role in decreasing inflammatory responses in IBD. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 86 publications
0
2
0
Order By: Relevance
“…Innate immune cells express Toll-like receptors (TLRs) responsible for the identification of pathogen-associated molecular patterns (PAMPs) and introduce an inflammatory immune response in response to them [78]. Sharifi and colleagues in 2019 showed a significant reduction in gene expression of TLR2 and TLR4 in an intestine cell-line, HT29, under an inflammatory condition and after curing the cells with mannuronic acid [79]. In the same year, Aletaha, et al showed that mannuronic acid can effectively prevent mRNA expression of TLR signaling molecules including MyD88 and NF-κB, in HEK293 cells triggered by a TLR2 agonist (LTA) and a TLR4 agonist (LPS); also, they showed that mannuronic acid decreased LTA and LPS-activated production of TNF-α and IL-6 inflammatory cytokines [80].…”
Section: Anti-inflammatory Effects Of Mannuronic Acid and Its Molecul...mentioning
confidence: 99%
“…Innate immune cells express Toll-like receptors (TLRs) responsible for the identification of pathogen-associated molecular patterns (PAMPs) and introduce an inflammatory immune response in response to them [78]. Sharifi and colleagues in 2019 showed a significant reduction in gene expression of TLR2 and TLR4 in an intestine cell-line, HT29, under an inflammatory condition and after curing the cells with mannuronic acid [79]. In the same year, Aletaha, et al showed that mannuronic acid can effectively prevent mRNA expression of TLR signaling molecules including MyD88 and NF-κB, in HEK293 cells triggered by a TLR2 agonist (LTA) and a TLR4 agonist (LPS); also, they showed that mannuronic acid decreased LTA and LPS-activated production of TNF-α and IL-6 inflammatory cytokines [80].…”
Section: Anti-inflammatory Effects Of Mannuronic Acid and Its Molecul...mentioning
confidence: 99%
“…M2000 is a new member of the group of immunosuppressive agents, with properties of nonsteroidal anti-inflammatory drugs [ 147 ]. The therapeutic benefits of M2000 include the treatment of oxidative stress and inflammation-related disorders such as diabetes, aging, neurodegeneration, inflammatory bowel disease, rheumatoid arthritis, tumors, and cardiac disorders [ 148 , 149 , 150 , 151 , 152 , 153 , 154 , 155 , 156 ]. M2000 showed protective effects against adjuvant-induced arthritis, experimental autoimmune encephalomyelitis, nephrotic syndrome, and acute glomerulonephritis during in vitro and in vivo examinations with maximum tolerance, and its efficacy was proved in various laboratory experimental models [ 157 , 158 , 159 ].…”
Section: Natural Biomolecules Targeting Jak/stat/socs Signaling In Ad...mentioning
confidence: 99%